2018
DOI: 10.1111/dom.13262
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic effects of metformin: From molecular mechanisms to clinical implications

Abstract: There is a growing body of evidence that links epigenetic modifications to type 2 diabetes. Researchers have more recently investigated effects of commonly used medications, including those prescribed for diabetes, on epigenetic processes. This work reviews the influence of the widely used antidiabetic drug metformin on epigenomics, microRNA levels and subsequent gene expression, and potential clinical implications. Metformin may influence the activity of numerous epigenetic modifying enzymes, mostly by modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(108 citation statements)
references
References 97 publications
0
106
0
2
Order By: Relevance
“…Emerging evidence has shown that metformin also has epigenetic functions, which has been reviewed elsewhere recently (Bridgeman, Ellison, Melton, Newsholme, & Mamotte, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Emerging evidence has shown that metformin also has epigenetic functions, which has been reviewed elsewhere recently (Bridgeman, Ellison, Melton, Newsholme, & Mamotte, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Metformin functions by inducing AMPK activity. While AMPK down‐regulates many factors involved in epigenetic regulation, it phosphorylates and activates Hat1 (Bridgeman, Ellison, Melton, Newsholme, & Mamotte, ). A primary target of Hat1 acetylation, histone H4 lysine 12, has also been linked to aging.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the metforminmediated inhibition of mitochondrial electron transfer, metformin is able to activate a variety of AMPK-dependent and -independent signaling pathways through which it facilitates the inhibition of mTOR, inhibits the inflammatory pathway, and lastly disturbs inflammation, cellular survival, stress defense, protein synthesis, autophagy, and epigenetic reprogramming . [13][14][15][16][17][18][19][20] Downstream of these major biological outcomes, metformin might have the capacity to impact all the cancerimmune system interactions constituting the so-called "cancer immunogram". 21 Metformin might lead to systemically decreased levels of pro-inflammatory soluble inhibitors (e.g., serum levels of C-reactive protein and IL-6 [22][23][24] ), which are known to drive tumor-associated inflammation, impair T cell-mediated tumor control, and associate with poor outcomes in response to ICIs (1).…”
Section: Metformin Enhances the Anti-tumor Functionality Of T-cellsmentioning
confidence: 99%